1st metatarsophalangeal joint fusion: A comparison of non-union and gender differences between locking and non-locking plating systems. Issue 4 (December 2015) - Bass, Edward James; Sirikonda, Siva Prasad
Highlights: The authors present a case series of 172 consecutive 1st MTP joint Fusions. The fusion rates of three different plating systems are compared. There was no significant difference between the groups. The difference in fusion rates between males and females was significant. Abstract: Background: Fusion of the first metatarsophalangeal joint (1st MTPJ) is a common surgical procedure used to treat a variety of diseases and deformities of the forefoot. Fixation methods vary and typically fusion rates are good. Objectives: The objectives of the study are to demonstrate whether there is any advantage to using locking as opposed to non-locking plates for 1st MTPJ fusion. Additionally the study aims to determine whether there is any difference in non-union rates according to gender. Methods: One hundred and seventy two consecutive 1st MTPJ fusions were performed for 153 patients. 40 patients (23%) were male and 132 (77%) female. Twenty patients received Hallu-fix ™ plates, 76 Charlotte TM plates and 76 Anchorage TM plates. Postoperative radiographs were reviewed for non-union. Failure rates were compared using Fisher's exact tests ( p = 0.05). Results: Twelve (6.9%) non-unions were identified. The difference in failure rates between all systems was not statistically significant. However, the difference in fusion rates between males (17.5%) and females (3.8%) was significant. Conclusion: This study finds that 1st MTPJ fusion is an effective method to treat diseases of the 1st MTPJ. Locking plates may offer better fusion rates than their non-locking counterparts. This is especially evident in male patients.